Beyond the gut: Skin microbiome compositional changes are associated with BMI. (August 2019) - Brandwein, Michael; Katz, Idan; Katz, Ariel; Kohen, Ron
Abstract: Microbiome compositional changes are associated with obesity in the gut. Emerging evidence points to a connection between gut and skin microbial communities. We hypothesized that skin microbiome compositional changes are associated with different BMI levels and that overweight or obese individuals would have reduced skin microbial diversity. We statistically analyzed gut, oral and skin microbiome samples to recapture previously observed partitioning between the microbiomes of these sites. We further analyzed 822 skin microbiome samples from the American Gut Project database and correlated BMI levels with community structure and composition using QIIME. Gut, oral and skin samples showed distinct community composition, and gut and skin microbial diversity was affected by BMI. Oral microbial diversity was not affected by BMI. Skin beta-diversity and community composition was correlated with BMI category, and Corynebacterium relative abundance was significantly correlated with BMI. In conclusion, non-cutaneous conditions affect the composition of the skin microbiome and the skin microbiome may therefore be used as a biomarker for disease manifestations beyond those with a cutaneous etiology.